Evaluasi Perbandingan Pengalaman Pengguna Computer Based Test Pada Test.co.id dan Quizizz Menggunakan Metode UEQ - Hil Dina Mulya Dewi; Asif Faroqi; Arista Pratama (STMIK Budi Darma, 2023)
Technology to develop rapidly in the education sector has been implemented to facilitate the implementation of learning processes. One example of its implementation is the use of Computer-Based Tests (CBT). CBT is a testing method where the arrangement of each answer response is stored and evaluated electronically. This research aims to evaluate the user experience in using the Test.co.id application and Quizizz application as Computer-Based Test (CBT) applications in SMAN 15 Surabaya. The main issue identified is the use of the Test.co.id application, accompanied by the introduction of the Quizizz application used by teachers for daily exams and quizzes. This does not align with the primary purpose of creating the Test.co.id application, which is to familiarize students with CBT applications in preparation for the national examination. This research evaluates the comparative user experience based on measurement scales using the User Experience Questionnaire (UEQ). The UEQ method consists of six measurement scales and 26 question items as instruments in the questionnaire. By using the Proportionate Stratified Random Sampling technique, the required sample size for this study is a minimum of 106 respondents. The results of this research indicate that both the Test.co.id and Quizizz applications have a positive impression with a fairly good average score on the six scales: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty, where each scale achieves an average value greater than 0.8. It can be concluded that the average values of both applications do not differ significantly. Overall, both applications have a positive impression on users in terms of user experience